Kajian Sosio Budaya Kumpulan Sajak Madura "Akulah Darahmu" Karya D. Zawawi Imron - Teguh Santoso (Humaniora, 2004)
Cultural complexity predicts not only more color terms in a society, but also a larger number of general terms for classifying plants and animals, for example, the poems written by Zawawi Imron who has Madurese background. One way a society's language may reflect its corresponding culture in its lexical content, or vocabulary. Experiences, events or objects singled out and given simple or single morph names may be a result of cultural characteristics.